Development Factors of Shipping Industry Special Zone to Support Regional Innovation System - Eko Budi Santoso; Ummi Fadlilah Kurniawati; Ajeng Nugrahaning Dewanti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2014)
The central government has established the industry road map through MP3EI to support the shipbuilding industry. The region of Surabaya, Gresik, Lamongan and Tuban areas will be developed as the national shipping industry. The purpose of this study is to f ormulate the shipbuilding industry development cooperation to support the development of regional innovation systems. The goal and objectives are to identify the type of support the shipbuilding industry in Lamongan, to obtain a general picture of the existing condition of shipbuilding industries and the subsequent descriptive analysis to identify factors that influence the development of the shipbuilding industry. The method is using a theoretical review of the literature and the descriptive analysis of the results of depth interviews with stakeholders in Lamongan. The results of this study are the factors that influence the development of the shipbuilding industry.